Densité agricole et charge humaine des terroirs : Essai méthodologique avec application à quatre comtés au sud de l’estuaire du Saint-Laurent - Raveneau, Jean (Cahiers de géographie du Québec, 1964)
The density of agricultural population based on cleared land does not necessarily express the real population pressure in a given agricultural region. Two factors can upset the significance of this measure of density : (1) differences in the intensity of exploitation within a single territory ; and (2), variations in the proportion of part-time farmers. The author bas developed an index of the pressure of population on the land by making various calculations for jour counties in Québec, on the south shore of the St. Lawrence estuary. He bas found that the population pressure on the land varies in nearly direct proportion to the agricultural density based on cleared land, in spite of the lack of uniformity of the physical environment in question. The author concludes that the agricultural density retains its validity for expressing the population pressure on the land.